2009
DOI: 10.1029/2009gl040959
|View full text |Cite
|
Sign up to set email alerts
|

Internal waves and short‐scale distribution patterns of chlorophyll in the Strait of Gibraltar and Alborán Sea

Abstract: A selection of ASAR images have been analyzed, together with instantaneous images of surface chlorophyll recorded with MERIS and MODIS, in order to study the relationship between the physical and biological processes associated with internal waves in the Strait of Gibraltar and Alborán Sea. The images show peak levels of chlorophyll at the coastal edges to the north and south of the Camarinal Sill (CS) during the generation of internal waves, and peak levels of chlorophyll associated with the wave fronts as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…This suggests that surface divergences and coastal suction are associated with these smaller topographic internal arrested waves typical of neap tides . These tongue-shaped structures were also found in satellite data by Vázquez et al (2009) during spring tides, but we present here the first evidence of this process during neap tides (Figures 5 C,F,I and 7 C).…”
Section: Physical Variablessupporting
confidence: 56%
See 3 more Smart Citations
“…This suggests that surface divergences and coastal suction are associated with these smaller topographic internal arrested waves typical of neap tides . These tongue-shaped structures were also found in satellite data by Vázquez et al (2009) during spring tides, but we present here the first evidence of this process during neap tides (Figures 5 C,F,I and 7 C).…”
Section: Physical Variablessupporting
confidence: 56%
“…This hypothesis was recently confirmed by Vázquez et al (2009), who used in-situ data and satellite images showing how the generation of internal waves induced transport of chlorophyll-enriched coastal waters to the channel and their advection towards the Alboran Sea. Bartual et al (2011) found evidence of a change in the plankton primary production pattern concomitant with the presence of an internal bore in the main channel of the strait, which was consistent with the arrival of active coastal plankton communities.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Based on sea surface roughness in sunglint area, these waves can also be imaged on high-resolution optical imagery (Apel et al 1985), such as Satellite Pour l'Observation de la Terre (SPOT) (Mitnik et al 2000). In addition, the chlorophyll images derived from ocean colour measurements of the Seaviewing Wide Field-of-view Sensor (SeaWiFS) and Moderate Resolution Imaging Spectroradiometer (MODIS) have also been successfully employed in the study of ISWs (da Silva et al 2002;Vázquez et al 2009;Pan et al 2012;Muacho et al 2013). However, the application of ocean colour images in studying ISWs is severely limited by their relatively low resolution (1.1 km) and, in some cases, by the interference of upwelling signatures at the ocean surface.…”
Section: Introductionmentioning
confidence: 99%